DUNIA MMO GAME PARA GAMER DI KOMUNITAS FORUM INDOGAMERS - Wawan Wartono (Linimasa : Jurnal Ilmu Komunikasi, 2022)
The number of gamers has increased rapidly during the Covid-19 pandemic. However, researchers in this regard tend to look at negative aspects such as addiction and mental health. It is very rare for research related to MMO Games or Online Games that examines and interprets games from the point of view of the experience and articulation of the gamers themselves. Researchers are trying to take a more neutral perspective or a middle ground in viewing this online game phenomenon through the research "The World of MMO Games for Gamers in the Indogamers Forum Community". How gamers (online game players) construct their world and how far they go and live their role in online games, is very interesting for researchers to explore further. This research is an online qualitative research using virtual ethnography and phenomenology. Virtual ethnography is used as an approach to reach the research location, while phenomenology is used to dig deeper into the experience of gamers. Research informants were selected purposively and snowballing. The number of informants in this study were 23 people consisting of various ages and genders. In general, how gamers' worlds are constructed and how far they (gamers) go and live their roles, depending on their category. Based on the research data processing that the researchers obtained, there were at least 5 categories that the researchers found, namely Newbie, Adventure, Admirer, Master, and Professional.